Effect of frying process on fatty acid composition and iodine value of selected vegetable oils and their blends - Serjouie, Alireza; Tan, Chin Ping; Mirhosseini, Hamed; Che Man, Yaakob (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The main objective of the present study was to investigate the effects of the frying media and storage time on the fatty acid composition (FAC) and iodine value (IV) of deep-fat fried potato chips. The frying experiment was conducted at 180ºC for five consecutive days. Six frying media were considered as the main treatments: refined, bleached, deodorized (RBD) palm olein (A), canola oil (C), RBD palm olein/sesame oil (AB, 1:1 w/w), RBD palm olein/canola oil (AC, 1:1, w/w), sesame oil/canola oil (BC, 1:1, w/w), and RBD palm olein/sesame oil/canola oil (ABC, 1:1:1, w/w/w). The initial degrees of unsaturation of the consumed oils, A, C, AB, AC, BC, and ABC, were 58.6, 94.0, 68.0, 72.2, 87.7, and 75.8 (g/100 g), respectively. The fatty acid analysis showed that there was a decrease in both the linolenic acid (C18:3) and linoleic acid (C18:2) contents, whereas the palmitic acid (C16:0) increased with a prolonged frying time. The chemical analysis showed that there was a significant (p < 0.05) difference in terms of the IV for each frying oil during the five consecutive days of frying (day 0 to 5). Oil C had the least stability in terms of deep-fat frying due to a high level of unsaturated fatty acids. Conversely, oil AC had the best stability due to the smallest reduction of the C18:2/C16:0 ratio and the IV.